Consoling the inconsolable? Writing, telling and persistent pain in Robert Arthur Alexie’s Porcupines and China Dolls - Franck MIROUX (E-REA)
This paper examines Gwich’in writer Robert Arthur Alexie’s 2002 novel Porcupines and China Dolls through the prisms of consolation and healing. It shows that Alexie challenges the widespread idea of reconciliation as a path towards closure. Drawing on both Indigenous and non-Indigenous critical theory, it contends that consolatory discourses as they appear in the novel do not guarantee full recovery but may even bring more pain by exposing too deep a wound to be mended. While this article stresses that the notion of inconsolability is a core issue in a narrative essentially concerned with the acceptance of loss, it also demonstrates that some degree of solace can be achieved through the restoration of a sense of tribal identity.